Study on effect of window grilles for safety purposes on heat transfer in a building - Amirul Ariffin, Bin Kassim (Universiti Malaysia Sarawak, UNIMAS, 2010)
Energy Efficiency is important to ensure our country’s natural resources are adequate for future generation. According to Malaysia Energy Centre (2009), commercial building is the second largest consumer of energy consumption. Nowadays, occupants tend to install window grilles as one of the safety features for their house. Safety window grilles can prevent or slowed down the burglars from entering house premises. The objective of this project is to study the effect of safety window grilles on the heat transfer into a building indirectly affect the energy usage for human comfort. The experiments on the effect of safety window grilles on the heat transfer in a building were conducted in rooms of Bunga Raya College located in UNIMAS. Results will consist of comparison between room with or without safety window grilles and validated by a dynamic thermal model software. Further results will commence through simulation to rectify or justify the effect of window grilles on heat transfer in a building through windows. The results of the study would contribute the knowledge of the significance effect of the usage of window grilles on heat transfer in a building to provide a cleaner and safety environment.